Islet-1 Immunoreactivity in the Developing Retina of Xenopus laevis - Guadalupe Álvarez-Hernán; Ruth Bejarano-Escobar; Ruth Morona; Agustín González; Gervasio Martín-Partido; Javier Francisco-Morcillo (The Scientific World Journal)
The LIM-homeodomain transcription factor Islet1 (Isl1) has been widely used as a marker of neuronal differentiation in the developing visual system of different classes of vertebrates, including mammals, birds, reptiles, and fish. In the present study, we analyzed the spatial and temporal distribution of Isl1-immunoreactive cells during Xenopus laevis retinal development and its relation to the formation of the retinal layers, and in combination with different markers of cell differentiation. The earliest Isl1 expression appeared at St29-30 in the cell nuclei of sparse differentiating neuroblasts located in the vitreal surface of the undifferentiated retina. At St35-36, abundant Isl1-positive cells accumulated at the vitreal surface of the neuroepithelium. As development proceeded and through the postmetamorphic juveniles, Isl1 expression was identified in subpopulations of ganglion cells and in subsets of amacrine, bipolar, and horizontal cells. These data together suggest a possible role for Isl1 in the early differentiation and maintenance of different retinal cell types, and Isl1 can serve as a specific molecular marker for the study of retinal cell specification in X. laevis.